PERANCANGAN SISTEM PELAPORAN AKUNTANSI PADA USAHA MIKRO KECIL MENENGAH (UMKM) SESUAI DENGAN SAK-ETAP DI WILAYAH MALANG (Studi Kasus pada Resto Gama Malang) - Rachmawati A, Intan (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2018)
The purpose of this research is to know about the application of accounting information system and reporting from Resto Gama. Resto Gama is a retoran or restaurant business that coincided in Watu Gong Malang city, started in design in 1993 and started operating in 1994 in Jember. The purpose of this restaurant opening to serve the high interest of the community, especially Brawijaya students in the field of culinary or culinary. This research uses descriptive qualitative approach where data will be analyzed descriptively from interview, and note from result of observation. Notes will be analyzed to systematically describe the focus of research which includes the design of accounting information systems and the draft of financial statements in accordance with the standards. Data analysis aims to describe the actual situation in the field. From the results of this study shows that the system is done by restaurant gama still less and should be evaluated. There is still a merger of jobdesk applied by gama. The accounting system at the restaurant is also less effective to run. This can be seen from the development and economic growth of Resto Gama Watugong which is considered slow.